2005
DOI: 10.1161/01.atv.0000151690.43777.e4
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Mobilizes Functional Endothelial Progenitor Cells in Patients With Coronary Artery Disease

Abstract: Objective— Endothelial progenitor cells (EPCs) that may repair vascular injury are reduced in patients with coronary artery disease (CAD). We reasoned that EPC number and function may be increased by granulocyte colony-stimulating factor (G-CSF) used to mobilize hematopoietic progenitor cells in healthy donors. Methods and Results— Sixteen CAD patients had reduced CD34 + /CD133 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(172 citation statements)
references
References 27 publications
9
161
1
1
Order By: Relevance
“…Also, the number of risk factors in their study was significantly correlated with a reduction of EPC levels (R ¼ À0.394, P ¼ 0.002) and CD34-/KDR-positive cells (R ¼ À0.537, P < 0.001) thus indicating individual confounding variables exist among patients. Pharmaceutical compounds also appear to stimulate (21) and perhaps inhibit EPC mobilization from the bone marrow (22,23). The purpose of our study was to design and test a strategy of measuring multiple populations of cells using multiparameter flow cytometry and not to clinically evaluate the effects of risk factors or medications on EPC number.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the number of risk factors in their study was significantly correlated with a reduction of EPC levels (R ¼ À0.394, P ¼ 0.002) and CD34-/KDR-positive cells (R ¼ À0.537, P < 0.001) thus indicating individual confounding variables exist among patients. Pharmaceutical compounds also appear to stimulate (21) and perhaps inhibit EPC mobilization from the bone marrow (22,23). The purpose of our study was to design and test a strategy of measuring multiple populations of cells using multiparameter flow cytometry and not to clinically evaluate the effects of risk factors or medications on EPC number.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, administration of G-CSF may worsen plaque formation and restenosis in coronary arteries. Enhancement of increased circulating granulocytes with G-CSF has been shown to induce adverse cardiovascular events, including acute coronary syndrome [18][19][20] . Kang et al 18) reported that G-CSF treatment might increase the progression of atherosclerotic plaque and in-stent restenosis in patients treated with primary percutaneous coronary intervention.…”
Section: Introductionmentioning
confidence: 99%
“…6 -9 However, it is known that G-CSF enhances the number of circulating granulocytes that potentially induces adverse cardiovascular events including acute coronary syndrome. 10,11 In earlier studies, Bussolino et al demonstrated that G-CSF stimulated angiogenic functions of mature endothelial cells (ECs), resulting in enhanced migration, proliferation and tube formation in vitro. 12,13 From the latter findings, we reasoned that low dose of G-CSF injected into local ischemic tissues would enhance neovascularization via direct stimulatory actions on endothelial cells.…”
mentioning
confidence: 99%